Forces and moments generated by aligner‐type appliances for orthodontic tooth movement: A systematic review and meta‐analysis. (9th July 2019) - Iliadi, Anna; Koletsi, Despina; Eliades, Theodore
Abstract: The aim of this review was to systematically appraise the evidence on aligner mechanics and forces and moments generated across difference types of aligners. In vitro‐ laboratory studies for model simulated tooth movement with aligners. Database searches within Medline via Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS via BIREME Virtual Health Library. Unpublished literature was also searched in Open Grey, ClinicalTrials.gov (www.clinicaltrials.gov ), the National Research Register (www.controlled-trials.com ) and Center for Open Science (Open Science Framework), using the terms "aligner" AND "orthodontic". Risk of bias assessment was based on the Cochrane Risk of Bias tool. Random effects meta‐analyses were conducted. A total of 447 studies were identified through electronic search and after careful consideration of pre‐ defined eligibility criteria, 13 deemed eligible for inclusion, while 2 were included in the quantitative synthesis. When palatal tipping of the upper central incisor through PET‐G aligners was considered, aligner thickness of 0.5, 0.625 or 0.75 mm was not associated with a significantly different moment to force (M/F) ratio, given a common gingival edge width of 3‐4 mm. Aligner thickness does not appear to possess a significant role in forces and moments generated by clear aligners under specific settings, while the most commonly examined tooth movements are tipping and rotation. The findings of this review may be applicable to certain conditions in laboratory settings.